As relações entre arte contemporânea, mediação e cultura visual: uma contribuição à pedagogia do imaginário - Bezerra, Paula Francinete Barros (2016)
The present study aims to reflect on the relationship between contemporary art, mediation and visual culture from the perspective of identifying possible contributions to the pedagogy of imaginary. The route proposed presents a theoretical review about the categories in question based on the authors Bachelard, Dewey, Araújo & Araújo, Teixeira, Wunenburger, Mirian Celeste Martins, Dias, Picosque, Raimundo Martins, Cocchiarale and Belidson, proposing a reflection on the imaginary, art and education; an extract of the context of contemporary art, highlighting some aspects of poetic imaginary present in artistic production from São Luís. It covers a survey of three prominent journals in the area of education and art: ANPED Brazilian Education Journal, Education and Society and Visuals on the categories under study in the temporal cut of 2000 to 2014. Discusses yet about the connections between visual culture and the cultural mediation in the contemporary context in art, interlacing concepts and experiences in the creative process of development of this research. Defines under which point of view the methodological path is traced, highlighting the experience as a starting point to guide them and the imaginary part of the construction of poetry of relations and processes of creation. As the North, he emphasizes a/r/tography as a methodological reference that relates the artist, the researcher and the educator as interconnected subjects in this process of analysis. Thus, the proposed reflection seeks to carry out a study of a hermeneutic phenomenological approach that if references in the new vision paradigmatic that proposes to overcoming the dichotomy between the sciences, suggesting a relationship between the categories cited by the analysis of narratives of mediators/educators and artists who work in the cultural scenario of São Luís-MA. Proposing also to construct possible paths for the pedagogy of the imaginary. Thus, 12 artists and 12 mediators / educators were selected, who act with expressiveness in the local scenario from 2014 to 2016, during the period of this research in the Master in Education of UFMA. Finally, it addresses the difficulties encountered in the process, the contributions of the perceptions and experiences of the path traveled, pointing to open dialogues for the continuity of the research.